From sacred to profane: traditions and innovations in soviet rituals - Julia Slootska (Cхід, 2013)
The article deals with process of creation Soviet rituals and its establishment. The paper includes the main stages of Soviet ritual's formation. This research shows reasons of needs of Soviet non-religious rituals system for Soviet society and USSR generally.